Photoshop effects for portrait photographers - Grey, Christopher (Focal Press/Elsevier, 2007)
Want to offer your clients more to chose from? Here's how: award winning photographer, Christopher Grey, has developed techniques to enhance portrait photography, using the creative applications available in Photoshop. Photoshop Effects for Portrait Photographers contains detailed explanations of how to replicate many darkroom techniques with Photoshop (Dodging, Burning, Vignettes, etc.) as well as camera and earlier technology techniques (Short Focus, High Speed Film Grain, Hand Coloring, etc.). Grey has also developed almost two dozen ways to replicate traditional painterly and illustrative.